Agriculture Research, Multistakeholder Partnerships and the SDGs - CSIRO; CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2016)
The Sustainable Development Goals (SDG’s) articulate the series of complex problems facing the world today. Addressing these will require systemic change: transformative, systems wide innovation involving inter-linked technological, institutional and policy change across scales.